Implementasi Kebijakan Indeks Desa Membangun (IDM) Di Desa Biringala Kecamatan Barombong Kabupaten Gowa - Aulia, Nurul; Madani, Muhlis; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2023)
This study purposed to find out the extent of development progress in Biringala Village through the implementation of the IDM Policy. The research method used qualitative to understand the abilities that were capable of being carried out by the research subjects, while the data collection techniques used the methods of observation, interviews, and document studies with a total of 8 informants. Data analysis techniques were data collection, data reduction, data presentation, and conclusions. Then the data validation techniques used were source triangulation, technical triangulation and theoretical triangulation. The results showed that the Policy Implementation of the Developing Village Index (IDM) in Biringala Village was appropriate and in accordance with the policy implementation method proposed by Van Meter and Van Horn, namely, Standards and policy targets/measures and policy objectives that had been understood and implemented, Resources which consisted of ADD, DD, and PAD, Characteristics of implementing organizations that were tailored to the needs of the economic, environmental and social resilience index, Attitudes of implementers who supported and implemented IDM, Communication between related organizations and implementation activities where each activity and decision were communicated with both by policy implementers to related organizations and finally the social, economic and political environment that supports the implementation of IDM policies in Biringala Village.